Unconventional twinning assisted by pyramidal II stacking faults - Yang Hu; Dennis M. Kochmann (Materials Research Letters)
Twinning significantly affects the deformation behavior of hexagonal close-packed Mg, so a thorough understanding of twin nucleation and growth mechanisms is required for enhancing the properties of Mg-based materials. The commonly observed [Formula: see text] tension twins have been traditionally linked to 〈c + a〉 dislocation dissociation, which results in zonal dislocations with large Burgers vectors several times that of a single twinning dislocation and some residual dislocations. Contrarily, our molecular dynamics simulations reveal [Formula: see text] twin nucleation from pyramidal II stacking faults through atomic shuffling without shear displacements. This introduces an alternative twin nucleation mechanism, different from the classically accepted mechanism of dislocation dissociation.